Peran Nilai Tarung Derajat dalam Pembentukan Sikap Anggota - Kae Irhan; Muhammad Nur Alif; Aam Ali Rahman (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the process of internalizing the life values of Tarung Derajat and their influence on the attitude formation of members of Satlat GIM Sumedang. The study employed a qualitative approach with a participatory ethnographic method. The participants consisted of Tarung Derajat instructors, coaches, and members of Satlat GIM Sumedang. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed using thematic analysis with the assistance of NVivo software through the stages of transcription, coding, categorization, and theme development. The results showed that members’ attitude formation occurred through a consistent habituation process involving training, the implementation of organizational rules, coaches’ role modeling, and the internalization of the philosophy of “muscle, brain, and conscience.” Values such as discipline, responsibility, emotional control, courage, and respect developed through repeated and structured training experiences. This study concludes that Tarung Derajat functions not only as a martial art but also as an effective medium for character education in shaping members’ positive attitudes. These findings contribute to the development of character education based on martial arts and can serve as a reference for fostering the moral development of the younger generation through non-formal sports activities. Future research is recommended to examine the effectiveness of internalizing martial arts values across broader age groups and social environments.    Keywords: Attitude Formation; Character Education; Life Values; Martial Arts; Tarung Derajat.